TINGKAT INFEKSI PARASIT Thaparocleidus sp. PADA INSANG IKAN PATIN (Pangasianodon hypopthalmus) - Hilal Anshary; Sriwulan Sriwulan; Junianto Talunga (Jurnal Perikanan Universitas Gadjah Mada, 2013)
Monogenean is a parasite group which most often causes serious disease in ﬁsh due to its direct life cycle, high reproductive potential, and high pathogenicity. The aim of this study was to investigate infection level of Thaparocleidus sp.onstriped catﬁ sh which infected catﬁ sh ﬁngerling. Striped catﬁ sh ﬁ ngerling with 5–10 cm in total length samples from three diferent ornamental ﬁsh supplier in Makasar were  examined. Sampling was conducted weekly for three weeks and 10 ﬁshes from each locations were collected. Samples were transported to laboratorium with aerated plactic bags and transported to Laboratory of Fish Parasite and disease for parasite examination. Organ which examined were gills. Prevalence of Thaparocleidus sp infection in all locations sampled was 100%. Mean intensity of the parasite infection was 98, 58 and 70 in location I, Location II, and Location III, respectively. The high prevalence and mean intensity of Thaparocleidus sp. infection indicated that health management in the aquaculture facilities was not properly implemented and this parasite existance is one of aquaculture problems to develop catﬁ sh fulﬁ lling ornamental or consumption demand .